BIOSTRATIGRAFI DAN BIODATUM FORAMINIFERA PLANKTONIK SUMUR-95 DI DAERAH CEPU KABUPTEN BLORA JAWA TENGAH - Sanyoto, Siwi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
Planktonic foraminiferals are used to identify locally, regionally and inter-regio-nally stratigraphic correlation. Due to stratigraphic correlation, using fossil is further applied in base on a number of biodatums. Based on planktonic foraminiferal analyses, within sixty-eight rock samples which were taken each 10 m for the interval, can be com-piled within three biodatums and one partially zone, i.e Globorotalia tosaensis tenuetheca biodatum, Glorotalia truncatulinuides truncatulinoides biodatum, and Globigerina calida calida biodatum; also partially zona of Globigerina calida-calida.